Efektivitas Metode Pembelajaran Berbasis Game dalam Meningkatkan Partisipasi Siswa pada Pendidikan Jasmani - Faris Pradana Kusuma; Jaya Prasetya Dharma (Atletik Karya: Jurnal Pendidikan dan Olahraga Aktual, 2024)
This study aims to measure the effectiveness of game-based learning methods in increasing student participation in physical education subjects. This study uses an experimental method with a pretest-posttest design on junior high school students. The results show that the game-based approach significantly increases student engagement, increases learning motivation, and helps in the development of motor skills.